Strength and Durability Parameters of Brick Aggregate Concrete Incorporating Rice Husk Ash as a Partial Replacement of Cement - Md. Abu Noaman; Md. Rezaul Karim; Md. Nazrul Islam; Md. Suman Mia (Advances in Materials Science and Engineering)
This study assessed the strength and durability parameters of brick aggregate concrete (BAC) incorporating rice husk ash (RHA) as a partial replacement of cement. For this, concrete cylinders (100 mm × 200 mm) were made with 0% (control) to 25% RHA as a partial replacement of ordinary Portland cement (OPC) at a mix proportion of 1 : 1.5 : 3 and a water-to-binder (w/b) ratio of 0.50. Specimens were immersed separately in normal water, 3% sodium chloride (NaCl), 5% sodium sulfate (Na2SO4), 5% magnesium sulfate (MgSO4), 1% hydrochloric acid (HCl), and 1% sulfuric acid (H2SO4) solutions for several immersion periods. The slump test results indicated that the workability of BAC containing RHA (RBAC) decreased about 29.69%–75.02% compared to control (0% RHA). After 90 days, the BAC containing RHA (up to 15% replacement) was found approximately 2.28%–6.64% greater compressive strength than that of control concrete. In addition, water absorption and porosity of RBAC were around 17.59%–40.73% and 12.12%–35.68% lower than that of control concrete, respectively. Similarly, RBAC (up to 25% replacement) exhibited roughly 35.62%–54.79% higher resistance against chloride attack and 0.39%–4.56% better resistance against Na2SO4 attack (up to 15% replacement), however, it exhibited inferior resistance against MgSO4 attack compared to control. Meanwhile, BAC with 10% RHA showed about 5.35% and 1.00% superior performance than that of control concrete against HCl and H2SO4 attack, respectively. The relationships between the strength and durability parameters of RBAC also suggested that RHA contributes to improving the strength and durability parameters of BAC.